Pengaruh Suku Bunga, PER, dan PBV Terhadap Harga Saham Perusahaan Sub Sektor Konstruksi Bangunan - Rosa Arbaningrum; Asep Muslihat (COSTING : Journal of Economic, Business and Accounting, 2021)
The study aims to determine how much influence of interest rate, PER, and PBV have on stock prices. The method used is descriptive verification with a quantitative approaches. Data were analyzed using multiple linear regression analysis. Based on the results of a descriptive analysis of the highest interest rate occurred in 2014-2015 while the lowest interest rate in the 2017. There are 5 building construction sub-sector companies that have PER industry average, while 4 other companies have PER above industry average. Furthermore, there are 4 companies that have the value of PBV below the industry average and 5 companies have PBV above the industry average. Then, there are 5 companies that have a share price above the industry average and 4 companies have the stock price below the industry average. Based on the result of verificative analysis that interest rate variable has no signification effect on stock price, while PER variable has no signification effect on stock price and PBV variable has signification effect on stock price. R square test result show that the interest rate, PER, and PBV has effect of 29,3% against the stock price so that remaining 71,7% is affected by other variables that are not researched. Keywords: Interest Rate; PER; PBV; Stock Price.